The solution is:
[tex]x=-1, y=2\frac{2}{3}[/tex]
Step-by-step explanation:
Given
2x+3y=6 Eqn 1
-4x+3y=12 Eqn 2
Subtracting equation 2 from equation 1
[tex]2x+3y-(-4x+3y)=6-12\\2x+3y+4x-3y=-6\\6x=-6\\Dividing\ both\ sides\ by\ -6\\\frac{6x}{6}=\frac{-6}{6}\\x=-1[/tex]
Putting x=-1 in equation 1
[tex]2x+3y=6\\2(-1)+3y=6\\-2+3y=6\\3y=6+2\\3y=8\\Dividing\ both\ sides\ by\ 3\\\frac{3y}{3}=\frac{8}{3}\\y=2\frac{2}{3}[/tex]
The solution is:
[tex]x=-1, y=2\frac{2}{3}[/tex]
Keywords: Linear equations
Learn more about linear equations at:
#LearnwithBrainly